Standardization of Islamic Education in Religious Value Education Orientation - Muhtar, Zainal; Iriantara, Yosal; Handayani, Sri; Wahyudin, Wahyudin; Yudianti, Maria (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
Education is part of the future investment. The goals of education at any time need to be revised and adapted to the demands of change. Government Regulation Number 32 of 2013 concerning National Education Standards (SNP) provides direction on the need to develop and implement eight national education standards, namely: content standards, process standards, graduate competency standards, educators and education personnel standards, facilities and infrastructure standards, management standards, financing standards, and educational assessment standards. This study aims to describe the standardization of Islamic education on the orientation of religious values education. The National Education Standards have been implemented in accordance with the scope of their responsibilities to date. Even so, there are still pros and cons in the SNP policy, one of the reasons for the pro group is that standardization serves as a guide for teachers in making global changes, while those who oppose explain that standardization of education is heavily influenced by business and political decisions.